Hydrogen Gas Sensor Based on Nanocrystalline SnO2 Thin Film Grown on Bare Si Substrates - Kadhim, Imad H.; Hassan, H. Abu; Abdullah, Q. N. (Nano-Micro Letters, 2015)
In this paper, high-quality nanocrystalline SnO2 thin film was grown on bare Si (100) substrates by a sol–gel method. A metal–semiconductor–metal gas sensor was fabricated using nanocrystalline SnO2 thin film and palladium (Pd) metal. The contact between Pd and nanocrystalline SnO2 film is tunable. Ohmic barrier contact was formed without addition of glycerin, while Schottky contact formed by adding glycerin. Two kinds of sensor devices with Schottky contact were fabricated (Device 1: 8 h, 500 °C; Device 2: 10 h, 400 °C). The room temperature sensitivity for hydrogen (H2) was 120 and 95 % in 1000 ppm H2, and the low power consumption was 65 and 86 µW for two devices, respectively. At higher temperature of 125 °C, the sensitivity was increased to 195 and 160 %, respectively. The sensing measurements were repeatable at various temperatures (room temperature, 75, 125 °C) for over 50 min. It was found that Device 1 has better sensitivity than Device 2 due to its better crystallinity. These findings indicate that the sensors fabricated on bare Si by adding glycerin to the sol solution have strong ability to detect H2 gas under different concentrations and temperatures.